Hand eczema and health‐related quality of life; a comparison of EQ‐5D and the Dermatology Life Quality Index (DLQI) in relation to the hand eczema extent score (HEES). (16th August 2013) - Lindberg, Magnus; Bingefors, Kerstin; Meding, Birgitta; Berg, Mats
Summary Background Health‐related quality of life (HRQoL) is associated with the extent and severity of hand eczema. We still lack a consensus about which HRQoL instrument to use as the standard, and how to measure the extent and severity of hand eczema. Objectives To compare the Dermatology Life Quality Index (DLQI) with EQ‐5D (a standardized instrument for use as a measure of health outcome), and to evaluate how the Hand Eczema Extent Score (HEES) relates to these instruments. Methods Ninety‐three patients (61 females) were included. The HEES was recorded by a dermatologist, and the DLQI and EQ‐5D by the patients. The results were analysed with factor analysis and non‐parametric statistics. Results The DLQI and EQ‐5D showed decreased HRQoL. Using factor analysis, we could not establish an association between the DLQI and EQ‐5D. There were, however, correlations between the DLQI and the HEES (0.31), the EQindex and the HEES (− 0.32), the DLQI and the EQVAS (− 0.62), and the DLQI and the EQindex (− 0.67) (the EQVAS and the EQindex are calculated from EQ‐5D). Conclusions We could not link factors in the DLQI to EQ‐5D, which has previously been done for SF‐36 (Short Form 36). On the basis of this, we cannot recommend EQ‐5D over SF‐36 for hand eczema studies. The DLQI correlates with the EQVAS and the EQindex, and can probably be used as an approximation for EQ‐5D. Our findings with the HEES are interesting, as it can be used by patients.